The Splınted Jasper Jumper Applıances For Class Iıı Skeletal, Dental And Functıonal Malocclusıon (Two Cases Reports) - A. İhya Karaman; Faruk Ayhan Başçiftçi; Sıddık Malkoç (Galenos Yayinevi, 2002)
Early treatment of class III malocclusions is an acceptable method. Several treatment philosophies and appliances were developed for this reason. The aim of this study is to introduce the fabrication of splinted Jasper Jumper appliance and to investigate the short-term effects of it in class III cases. At the end of the treatment, favourable dental and skeletal changes were observed in both jaws. Splinted Jasper Jumper can be accepted as a different treatment choice in these kinds of patients.